Intraepithelial tumour infiltrating lymphocytes are associated with absence of tumour budding and immature/myxoid desmoplastic reaction, and with better recurrence‐free survival in stages I–III colorectal cancer. Issue 2 (14th September 2020) - González, I A; Bauer, P S; Liu, J; Chatterjee, D
Abstract : Aims: Tumour budding (TB), desmoplastic reaction (DR) and intraepithelial tumour infiltrating lymphocytes (iTILs) are recently recognised prognostic factors in colorectal cancer (CRC). In this study, we evaluated their significance and relationship to each other and their cumulative effect on survival. Methods and results: A total of 372 stages I–III CRC cases from 2013 to 2016 were included. Low TB was identified in 302 (81%) cases, immature/myxoid DR in 67 (18%) cases and iTILs in 130 (35.0%) cases. iTILs was associated with low budding ( P = 0.0247), non‐myxoid DR ( P = 0.0004), poorly differentiated histology ( P = 0.0015), absence of perineural invasion ( P = 0.0367) and loss of mismatch repair proteins ( P = 0.0002). Absence of iTILs and presence of immature/myxoid DR were associated with a worse recurrence‐free survival (RFS) [hazard ratio (HR) = 2.191, 95% confidence interval (CI) = 1.232–3.895; and HR = 5.706, 95% CI = 3.632–8.964, respectively]. A competing risk analysis showed statistically significant prognostic groups combining iTILs and TB ( P < 0.0001). Cases with iTILs and low TB were associated with better RFS compared to cases without iTILs and with intermediate/high TB (HR = 0.214, 95% CI = 0.109–0.421). Similarly, combining iTILs and DR revealed statistically significant prognostic groups ( P < 0.0001). Cases with iTILs and a non‐myxoid DR had better RFS compared to cases without iTILs and immature/myxoid DR (HR = 0.113, 95% CI = 0.056–0.230). On multivariate cause‐specific analysis, patients' age ( P = 0.0045), iTILs ( P = 0.0345), DR ( P < 0.0001) and pTNM prognostic groups ( P < 0.0001) were associated with RFS. Conclusions: Our study validates the association of iTILs and DR as independent prognostic finding in CRC, and propose a prognostic model using the combinations of iTILs with TB and stromal reaction in CRC.